KINETIC MODELING OF SERIES REACTION CH4-CH3OH-DME WITH CuO-ZnO/gamma-Al2O3 CATALYST - Chumaidi, Achmad; Moentamaria, Dwina; Murdani, Anggit (Universitas Negeri Semarang, 2018)
A kinetic model was proposed for the synthesis of methane to be dimethyl ether (DME) in one reaction step from (CH4 + O2) and (CH3OH) to dimethyl ether using kinetic CuO-ZnO /gAl2O3 catalyst parameters. The bifunctional catalyst of the series kinetic reaction model according to the experimental results obtained under isothermal conditions in a pipe flow reactor under various operating conditions: 225-325 ° C; 10 bar gauge; Residence time, 16-57.0 (g Catalyst) hour (mole CH4) -1. An important step for modeling is the synthesis of methanol from (CH4 + O2) and the synthesis of (CH3OH to DME) is methanol dehydration (very fast), and water-shifting and CO2 (equilibrium) reactions. The effects of water inhibition and CO2 were also taken into account in the synthesis of methanol and the formation of hydrocarbons. The dehydration advantage of methanol can achieve higher yields above 60 % methanol that was converted to DME and the remaining 5% methanol if (CH4 + O2) comes in at 10 bar gauge and 375 ° C. At higher temperatures produces CO2 and H2O. Methane-methanol-DME series reaction model follows single-order gas phase reaction to methane and methanol with k1 = 0.195 minutes-1 and k2 = 0.115 minutes-1 The time and maximum concentration occurs in the formation of methanol constituents 9.5 minutes and 0.44 mole